Hyperhydration and glycerol: Thermoregulatory effects during exercise in hot climates - Latzka, W. A.; Sawka, M. N. (Canadian Journal of Applied Physiology, 2000)
Hyperhydration or increasing body water content above normal (euhydration) level was thought to have some benefit during exercise heat-stress; however, attempts to overdrink have been minimized by a rapid diuretic response. The perception that hyperhydration might be beneficial for exercise performance and for thermoregulation arose from the adverse consequences of hypohydration. Many studies had examined the effects of hyperhydration on thermoregulation in the heat; however, most of them suffer from design problems that confound their results. The design problems included control conditions not representing euhydration but hypohydration, control conditions not adequately described, cold fluid ingestion that reduced core temperature, and/or changing heat acclimation status. Several investigators reported lower core temperatures during exercise after hyperhydration, while other studies do not. Some investigators reported higher sweating rates with hyperhydration, while other studies do not. Recent research that controlled for these confounding variables reported that hyperhydration (water or glycerol) did not alter core temperature, skin temperature, whole body sweating rate, local sweating rate, sweating threshold temperature, sweating sensitivity, or heart rate responses compared to euhydration trial. If euhydration is maintained during exercise-heat stress then hyperhydration appears to have no meaningful advantage.